Farm-Level Impacts of Greenhouse Gas Reductions for the Predominant Production Systems in Northern Nigeria - Ayinde, Taiwo B.; Ahmed, Benjamin; Nicholson, Charles F. (Springer, 2020)
This chapter summarizes the sources of greenhouse gas (GHG) emissions from different economic sectors in Nigeria and emphasizes those arising from agriculture and forestry. The impacts of climate change on agricultural systems in Nigeria are likely to be large, motivating the need for additional knowledge to assess current practices and formulate appropriate modifications for both mitigation and adaptation. Some current farming practices are believed to be adaptive, but further study would provide better assessments. We also analyzed the trade-offs between household income and GHG emissions at two contrasting sites in northern Nigeria. A farm optimization model maximizing the value of crop, livestock, and tree production activities in a single representative year assessed the potential impacts for GHG reductions of 10% and 25% and the maximum allowable reductions of 26% and 30% on farm activities and income. Emissions reductions of 10% reduced annual household incomes by less than 5% but required substantive changes, especially in livestock owned. Maximum possible GHG emissions reductions (while still meeting minimum household consumption needs) would require marked changes in production pattern and would lower household incomes by 22–44%. We did not assess effects over longer periods, where the role of livestock as a key asset may imply additional negative impacts. Productivity-enhancing technologies that would simultaneously reduce GHG emissions and increase incomes are needed for smallholder farms to play a larger role in climate change mitigation without the burden of reduced incomes and greater risk. This suggests the need for programmatic and policy actions both by national agricultural research systems and the Consultative Group for International Agricultural Research (CGIAR).